Ethic and Morality: Framing Analysis on Monetary Issue and Health Capitalism on Online News - Bob Wahyudin; Nurannafi Farni Syam Maella; Iwan Joko Prasetyo (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Contemporary media analysis makes great study in the junction of ethics, morality, financial concerns, and health capitalism. Using Entman's Framing Analysis Model to expose the underlying stories and prejudices, this research investigates how online news sites address certain subjects. The study begins by setting the scene for the relevance of moral and ethical considerations in debates on health capitalism and financial policies, especially in the digital age where public opinion and policy debates are much influenced by online news. The study of the literature explores the body of current work on media framing, ethical standards in journalism, the presentation of financial concerns, and the dynamics of health capitalism. The study draws attention to the areas in which the literature lacks in terms of how these subjects are handled on internet news and the possible influence on public opinion and policy-making. The study examines a range of online news items from major news sources using Entman's Framing Analysis Model. The elements of the model—problem characterization, causal interpretation, moral evaluation, and treatment recommendation—offer an analytical framework to look at how these publications tackle financial concerns and health capitalism. The results show obvious trends in how these subjects are presented on online news. Emphasizing the functions of government and financial institutions, monetary problems are often considered in connection with economic stability and the efficiency of policies. Still, health capitalism is most usually understood in terms of personal responsibility and market efficiency. It centers on moral conundrums and assessments of ethical issues related to affordable healthcare. The study has several connotations. It underlines the need of reporting on financial and health issues using a more fair and ethical sound manner. This emphasizes how public opinion and policy decisions could be influenced by media frame. It underlines the need of more responsibility in journalism to guarantee that difficult problems are presented in an ethical and instructive way.